Veracity model of survey based on an Android application for urban and rural zones - Luque Fernández, Álvaro Oswaldo (2019)
The consulting companies that are engaged in market research and the development of public and private projects are facing the excessive time spent in the field, which results in the loss of customers and under the commitment of the services that are offered. During the data collection, there is a non-sample error, which comes from the interviewee, where they are not sufficiently objective and sincere with their performance on the survey. For this study we consider the veracity patterns to admit a survey that can come from: questionnaires, scales or inventories. The objective of this study was to develop an android application that allows to elaborate a veracity model of surveys in urban and rural areas. In this context, the research shows a solution based on a model of veracity of surveys, which is based on an android application and that can be used in any District, it also allows to perform supervisions on the personnel (pollsters) that perform field work and finally to monitor the assessment under population parameters. The present research, according to the characteristics of the problem is of an applied type of relational level and experimental design, the population study was concentrated in the Ancocala and Calacala CPMs of the Cairani district of the province of Candarave, with a sample of 96 households, the informant being the head of household, therefore the sample is non-probabilistic and for convenience, since it will only serve to verify the degree of veracity of the survey. It was possible to apply programmable patterns in an android application to generate a model of veracity of surveys (87.50% of truthfulness and 12.50% of lies in the applied surveys). It is concluded that the traditional method failed to detect the sincerity in the performance of the surveys based on the socioeconomic levels.